EFFECTIVENESS OF LAW NUMBER 4 OF 2024 CONCERNING THE WELFARE OF MOTHERS AND CHILDREN IN THE FIRST THOUSAND DAYS OF LIFE - Agustina, Dwi Ayu; Nurlaili, Elly; Septiana, Dewi; Aprilianti; Sekar D.K, Sayyidah (Sriwijaya Crimen and Legal Studies, 2025)
Law Number 4 of 2024 concerning Maternal and Child Welfare is a form of the state's constitutional commitmentto guaranteeing the protection and fulfillment of the rights of mothers and children, especially during the first thousand days of life (1000 HPK), which is the golden period of growth and development for children. However, the effectiveness of its implementation cannot be said to be optimal, especially inremote, outermost, and disadvantaged areas. This study aims to evaluate the initial level of effectiveness and identify factors that hinder the implementation of the law. This study uses a normative-empirical legal approach based on Soerjono Soekanto's Theory of Legal Effectiveness. Data was obtainedthrough a literature study of legislation, academic literature, policy reports, and secondary data from government agencies. The resultsof the study show that the effectiveness of Law Number 4 of 2024 is still formal and procedural in nature, due to the weak binding force of legal substance, overlapping authority between institutions, limited resources, and a low legal culture and literacy among the community. Thus, the effectiveness of the law has not yet reached a substantive dimension that guarantees equitable welfare for mothers and children in 3T areas. This study recommends strengthening norms through sanctions and accountability mechanisms, cross-sector institutional integration, and the development of a legal culture based on community literacy as prerequisites for the successful implementation of just laws.